HIV transmission risk among people living with HIV in Zhejiang Province, China: data from a large cross-sectional study, 2022 - He, Lin; Pan, Xiaohong; Yang, Jiezhe; Zheng, Jinlei; Cheng, Wei; Chai, Chengliang (Frontiers in Public Health, 2025)
BackgroundEffective management of people living with HIV (PLWH) can block the sexual transmission as there is a zero risk of sexual transmission (by U=U campaign); however, few studies have aimed to addressed the risk of transmission among PLWH in China.MethodWe conducted a cross-sectional survey among PLWH in 2022. PLWH were categorized into four HIV transmission risk groups: on antiretroviral therapy (ART) and HIV viral load (VL) < 50 copies/mL as minimum risk; on ART and 50 ≤ VL < 1,000 copies/mL as low-risk; on ART and VL ≥ 1,000 copies/mL, or on ART but without VL testing as medium-risk; not on ART as high-risk. Multivariable logistic regression was used to identify risk factors associated with risk of HIV transmission.ResultA total of 39,744 PLWH were enrolled in the study. The proportion of those at risk for HIV transmission was 11.4%: low-risk 3.4%, medium-risk 6.9% and high-risk 1.1%. 33,764 (95.0%) patients were tested for syphilis, of whom 5.6% (1,879) had a current syphilis infection. Multivariable logistic regression analysis showed that compared with patients at minimum risk of transmission, individuals who were male (adjusted odds ratio [aOR]: 1.17, 95% confidence interval [CI]: 1.06–1.29), 16–24 age group (aOR: 2.13, 95% CI: 1.75–2.60), primary school or literate (aOR: 1.50, 95% CI: 1.36–1.65), heterosexual route of HIV infection (aOR: 1.50, 95% CI: 1.38–1.63), with a non-local registered residence (aOR: 1.55, 95% CI: 1.39–1.72), current CD4 + T count ≤200 cells/μL (aOR: 5.03, 95% CI: 4.52–2.59), and follow-up years less than 2 years (aOR: 2.02, 95% CI: 1.77–2.30) were associated with increased odds of HIV transmission. Being married (aOR: 0.62, 95% CI: 0.55–0.69) was associated with a decreased risk of HIV transmission.ConclusionWe concluded that 8.0% of PLWH were at moderate to high risk for HIV transmission. 88.6% of HIV positive patients in Zhejiang province, China were found to be at minimum risk of HIV transmission. Promoting HIV knowledge and education among younger adults, while linking individuals to ART to reduce their viral load could help reduce the persistently risk of HIV transmission.